Katyn [videorecording (DVD)] - Wajda, Andrzej, 1926-2016; Chyra, Andrzej, 1964-; Ostaszewska, Maja, 1972-; Żmijewski, Artur, 1966-; Mularczyk, Andrzej, 1930- (Koch Lorber Films ; distributed by E1 Entertainment, 2009)
Dramatization of the massacre of 20,000 people (interned Polish officers as well as civilians accused of treason by the occupying Soviet forces) by the Soviet secret police at Katyń in the spring of 1940, and the cover-up that followed. Follows the fictional stories of four families, separated from one another in the confusion of September 1939, when the Soviets and Germans invaded Poland, through the Soviet occupation in 1945 when the truth of the massacre gets suppressed.